Daesh’ Atrocities Against Women and Girls and The Necessary Response - Ewelina U. Ochab (Chrześcijaństwo-Świat-Polityka)
Since 2014, Daesh has been perpetrating mass atrocities against the population of Syria and Iraq, and beyond, and especially, crimes targeting religious minorities in Syria and Iraq. These included atrocities specifically targeting women and girls, including, rape, sexual abuse, and sexual slavery, and many more. Nonetheless, Daesh fighters are not being prosecuted for such crimes against women and girls and their (few) prosecutions are being conducted for terror-related offences only. The paper explores the use by Daesh of rape and sexual violence against minority women and girls. It considers some of the evidence of the use of rape and sexual violence in conflict, and most specifically, in the case study regarding the genocide committed by Daesh. It further examines the necessary changes that need to happen to address the issue. This includes an analysis of what legal measures have been taken to date to bring the Daesh perpetrators to justice, and specifically, for their atrocities perpetrated against women and girls.